Temperature-Sensitive Alleles of RSW2 Link the KORRIGAN Endo-1,4-β-Glucanase to Cellulose Synthesis and Cytokinesis in Arabidopsis - Lane, Diana R. (American Society of Plant Physiologists, 2001)
An 8.5-kb cosmid containing the KORRIGAN gene complements the cellulose-deficient rsw2-1 mutant of Arabidopsis. Three temperature-sensitive alleles of rsw2 show single amino acid mutations in the putative endo-1,4-β-glucanase encoded by KOR. The F(1) from crosses between kor-1 and rsw2 alleles shows a weak, temperature-sensitive root phenotype. The shoots of rsw2-1 seedlings produce less cellulose and accumulate a short chain, readily extractable glucan resembling that reported for rsw1 (which is defective in a putative glycosyltransferase required for cellulose synthesis). The double mutant (rsw2-1 rsw1) shows further reductions in cellulose production relative to both single mutants, constitutively slow root growth, and enhanced temperature-sensitive responses that are typically more severe than in either single mutant. Abnormal cytokinesis and severely reduced birefringent retardation in elongating root cell walls of rsw2 link the enzyme to cellulose production for primary cell walls and probably cell plates. The Rsw2(−) phenotype generally resembles the Kor(−) and cellulose-deficient Rsw1(−) phenotypes, but anther dehiscence is impaired in Rsw2-1(−). The findings link a second putative enzyme activity to cellulose synthesis in primary cell walls of Arabidopsis and further increases the parallels to cellulose synthesis in Agrobacterium tumefaciens where the celA and celC genes are required and encode a putative glycosyltransferase and an endo-1,4-β-glucanase related to RSW1 and KOR, respectively.